Perencanaan Instalasi Penerangan Jalan Umum Pada Jl. Sungai Kapih Kecamatan Sambutan Samarinda: Indonesia - Rizky Aprylianto Susilo (J-ENSITEC (Journal of Engineering and Sustainable Technology), 2023)
The installation of public street lighting serves as a tool for road users when they are active at night and increases the safety and comfort of road users from crime or unwanted things and also complements the road that can be placed on the right / left or the middle of the road (median) as well. Planning for public street lighting on SungaiKapih road uses LED lights with a power of 60 watts with a protection index (IP) of 65 and has an efficacy of 5 lux which produces a light intensity of 605 Cd. The lamp poles used are galvanized iron poles, the type of lamp poles used is a single-arm octagonal lamp post with a height of 11 meters, installed on the right side of the road parallel to a distance of 40 meters as many as 35 poles. The source of electricity used in the planning of Jalan Sungai Kapih lighting is a source from PLN which is located around the location. The control system for planning the SungaiKapih road uses an automatic and manual system that is controlled by a photocell, contactor and selector switch. The purpose of installing this selector is so that the circuit can still be operated if the timer and photocell are damaged or not functioning and make it easier for related parties to carry out maintenance or repairs on street lights.